Pharmacophore modeling for the identification of small-molecule inhibitors of TACE - Liu, Li-Juan (2016)
Tumor necrosis factor α-converting enzyme (TACE) plays a critical role in diverse physiological processes such as inflammation, hematopoiesis, and development. In this study, a pharmacophore model constructed from a training set of TACE inhibitors was used to screen an in-house database of organic compounds, from which compound 1 emerged as a top candidate. In a cell-free assay, compound 1 inhibited TACE enzymatic activity in a dose-dependent manner. Moreover, compound 1 inhibited the production of soluble TNF-α in human acute monocytic leukemia THP-1 cells without impacting nitric oxide production, and exhibited anti-proliferative activity against THP-1 cells. We envisage that compound 1 may be employed as a useful scaffold for the development of more potent TACE inhibitors. This study also validates the use of pharmacophore modeling to identify enzyme inhibitors.